The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41467-019-13482-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and detectability of the bridgmanite to post-perovskite transformation in the Earth's D″ layer

Abstract: Bridgmanite, the dominant mineral in the Earth’s lower mantle, crystallizes in the perovskite structure and transforms into post-perovskite at conditions relevant for the D layer. This transformation affects the dynamics of the Earth’s lowermost mantle and can explain a range of seismic observations. The thickness over which the two phases coexist, however, can extend over 100 km, casting doubt on the assignment of the observed seismic boundaries. Here, experiments show that the bridgmanite to post-perovskite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Post‐perovskite should be predominant above the CMB including such areas away from the circum‐Pacific high‐velocity regions. Our results do not preclude the bridgmanite/post‐perovskite transition in pyrolite from generating D” reflections; stress‐induced re‐equilibration within the two‐phase region can produce high amplitude seismic reflections, even when the transition region is thick (Langrand et al., 2019). Additionally, development of the lattice‐preferred orientation of post‐perovskite may generate sharp reflectors within a broad two‐phase region (Ammann et al., 2010; Pisconti et al., 2019).…”
Section: Discussionmentioning
confidence: 58%
“…Post‐perovskite should be predominant above the CMB including such areas away from the circum‐Pacific high‐velocity regions. Our results do not preclude the bridgmanite/post‐perovskite transition in pyrolite from generating D” reflections; stress‐induced re‐equilibration within the two‐phase region can produce high amplitude seismic reflections, even when the transition region is thick (Langrand et al., 2019). Additionally, development of the lattice‐preferred orientation of post‐perovskite may generate sharp reflectors within a broad two‐phase region (Ammann et al., 2010; Pisconti et al., 2019).…”
Section: Discussionmentioning
confidence: 58%
“…However, dynamic compression occurs on a timescale that largely prevents diffusive processes that change bulk alloy concentrations like those used to form steels. Recent studies in other materials have revealed diffusive phase transformations active on timescales as fast as tens of nanoseconds using dynamic compression 43 and can evolve with characteristic times on the order of hundreds of seconds or more using static compression 44 , highlighting a broad range of possible behaviors. In our case, the rapid stabilization of the hcp structure for iron and for Fe-Si 8.5wt% , but not for Fe-Si 16wt% , may imply that in this latter case the formation of hcp phase may require non-Martensitic action like diffusive de-mixing.…”
Section: Discussionmentioning
confidence: 99%
“…PETRA III serves a broad user community, covering a very broad range of scientific fields, from physics [1][2][3][4], chemistry [5,6], and biology, to medicine [7,8], materials [9][10][11], geo- [12][13][14][15] and environmental [16,17] science, archaeometry [18], and nanotechnology [19,20]. With this, it makes an important contribution to solving the grand societal challenges, e.g.…”
Section: Petra III Scientific Programmementioning
confidence: 99%